2022
DOI: 10.1097/brs.0000000000004490
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Models for Length of Stay and Discharge Disposition in Elective Spine Surgery: Development, Validation, and Comparison to the ACS NSQIP Risk Calculator

Abstract: Study Design. A retrospective study at a single academic institution.Objective. The purpose of this study is to utilize machine learning to predict hospital length of stay (LOS) and discharge disposition following adult elective spine surgery, and to compare performance metrics of machine learning models to the American College of Surgeon's National Surgical Quality Improvement Program's (ACS NSQIP) prediction calculator. Summary of Background Data. A total of 3678 adult patients undergoing elective spine surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Other discriminators of the present classification tree included age, intraoperative blood loss, delayed ambulation, and weight, similar to our regression analysis and some prior studies [ 13 , 18 , 24 , 25 ]. In a retrospective multicenter database analysis, Arora et al [ 11 ] performed a decision tree analysis and found that advanced age, obesity, and greater surgical invasiveness were significant variables increasing the likelihood of readmission and prolonged LOS. To reduce the incidence of postoperative AEs, in older patients (aged 79 years or older) who undergo long-segment fusion, hemostatic agents and minimally invasive surgery should be used to reduce intraoperative bleeding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other discriminators of the present classification tree included age, intraoperative blood loss, delayed ambulation, and weight, similar to our regression analysis and some prior studies [ 13 , 18 , 24 , 25 ]. In a retrospective multicenter database analysis, Arora et al [ 11 ] performed a decision tree analysis and found that advanced age, obesity, and greater surgical invasiveness were significant variables increasing the likelihood of readmission and prolonged LOS. To reduce the incidence of postoperative AEs, in older patients (aged 79 years or older) who undergo long-segment fusion, hemostatic agents and minimally invasive surgery should be used to reduce intraoperative bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…Many independent variables are associated with postoperative AEs following lumbar fusion surgery. Variables associated with increased length of stay (LOS) include increased age, morbid obesity, diabetes, opioid use, greater number of comorbid conditions, unemployment, drain use, and blood transfusion [ 9 11 ]. Older and non-married patients, those with obesity, positive smoking history, longer procedure times, and emergent cases were significantly more likely to be readmitted for complications or physical rehabilitation [ 9 , 10 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…[15]. Similarly, Arora et al developed a well-performing model that predicts patient discharge to rehabilitation, achieving high AUROC, sensitivity, and specificity with an adjusted threshold of 0.16 [32]. Both studies also demonstrated well-calibrated models through calibration plots.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 98%
“…93 ML can utilize intraoperative surgical details and a patient's socioeconomic factors to predict inpatient LOS. [94][95][96][97][98] This was performed in a 63 533-patient cohort after anterior lumbar and posterior lumbar interbody fusion, transforaminal lumbar interbody fusion, and posterior spine fusion. 98 To predict the time of discharge, models have been developed for patients after spinal fusion [99][100][101] and surgery for degenerative spondylolisthesis, 102 disk disorders, 103 and spinal stenosis.…”
Section: Length Of Staymentioning
confidence: 99%